Exploratory and confirmatory factor analysis of the sensitivity to punishment and sensitivity to reward questionnaire-revised and its psychometric evaluation among Chinese person with substance use disorder - Li, Shuying; Xie, Dongdong; Li, Meiting; Che, Qingqing; Zhang, Jun; Luo, Xingwei; Cai, Taisheng (Frontiers in Psychology, 2024)
The Sensitivity to Punishment and Sensitivity to Reward Questionnaire (SPSRQ) is a self-report tool widely used to assess individuals' level of reinforcement sensitivity. Drug addiction is strongly associated with reinforcement sensitivity, but there is a lack of measurement tools to assess reinforcement sensitivity in drug users, necessitating the revision and application of the SPSRQ among drug users. This study recruited 819 drug users (mean age = 34.74; 56.41% female) from five compulsory rehabilitation centers in Hunan Province, China. The applicability of the SPSRQ among person with substance use disorder was assessed by conducting reliability analyses and validity analyses, with retesting performed by 127 individuals after 6 weeks. Exploratory factor analysis for the SPSRQ showed a stable two-factor structure in person with substance use disorder. Confirmatory factor analysis indicated acceptable goodness of fit indexes for the two-factor structure. The SPSRQ also demonstrated good reliability and convergent and discriminant validity evidence. The two-factor structure of the SPSRQ also demonstrated measurement invariance across gender. Further comparative analysis found that the degree of reward sensitivity was higher for males than for females. Generally, the SPSRQ has shown evidence of good reliability and validity in Chinese drug-dependent populations, and it is suitable for research and application with Chinese person with substance use disorder. These findings about the personality traits of people with substance use disorder provide a solid basis for further research.